A dual-channel switching mechanism for uncertain NCSs against DoS attacks. (3rd February 2022) - Zhang, Qingcao; Yin, Xiuxia; Hu, Songlin
Abstract: In this paper, the stabilization mechanism, dual-channel switching mechanism, is investigated for a class of discrete-time networked control systems with parameter uncertainties and cyber attacks. A novel dual-channel switching mechanism is proposed against the denial-of-service attacks and achieve system asymptotic stability. The event-triggered scheme is considered to control unnecessary data communications. Based on this, a memory-based event-triggered scheme is put forward to overcome the drawback of event-triggered scheme so that the system dynamic performance is greatly improved and the network resources are saved also. Using the Lyapunov theory and linear matrix inequality, two sufficient conditions of memoryless and memory-based closed-loop systems are, respectively, derived to guarantee the desired stability. Furthermore, the controller gain(s) and event-triggered matrix are co-designed. Finally, the effectiveness of the proposed method is verified by the pendulum system and the satellite control system.